Biochemical Basis of Collagen Defect: Keloids - Ale, Ebenezer Morayo; Asuelimen, Steve Osagie; Andeuka, Useni Ajiya; Umaru, Isaac John; Umaru, Kerenhappuch Isaac (African Journal of Biochemistry and Molecular Biology Research, 2024)
Obscure in their genesis, keloids are benign fibro-proliferative disorders. They take place as a result of disturbances in the typical wound healing process in vulnerable people. Transforming Growth Factor beta (TGF-ß) family members have been linked to the pathogenesis of this illness, despite the fact that many other factors have been hypothesized to contribute to its aetiopathogenesis. Finding the right therapeutical notion requires understanding the differences between hypertrophic scars, keloids, and typical scars. Even though keloids are rather common in the general population, the mechanisms that cause keloid formation are still poorly understood. The fact that there are numerous treatment modalities reflects the reality that no single treatment has consistently demonstrated to be highly successful. New pathophysiological theories for keloid formation are revealed by improvements in our understanding of the wound healing process. This review distinguishes between keloids and hypertrophic scars, provides an overview of physiological wound healing, examines current theories for keloid formation, and describes the etiology of scar formation. This knowledge could aid in unraveling the complicated keloid etiology and aid in the creation of a successful treatment approach.